Measuring service quality of Universiti Teknologi MARA Puncak Perdana Library using LibQUAL / Noor Dina Mohd. Noor and Raja Abdullah Yaacob - Mohd. Noor, Noor Dina; Yaacob, Raja Abdullah (Faculty of Information Management, 2014)
This study focuses on library students as a yardstick for determining the level of service quality offered by the library. Academic libraries are facing two major challenges, namely global digital environment, and the increasing competition. Alternative approaches to measure quality emerge in the business sector. Specifically, through marketing research the SERVQUAL has evolved as an instrument in measuring service quality and what customers value as important. Modification of SERVQUAL model applied to measurements LibQUAL the quality of library services. LibQUAL was developed as an instrument to measure quality services by Zone of Tolerance. This instrument determines customers' expectations with the two-gap measures, the gap between the perceived service levels with the minimum service level (Service adequacy gap) and the gap of the perceived service level with the desired service level (Service superiority gap). The main objective of this research were to identify the level of service quality at Perpustakaan Tun Abdul Razak (PTAR) Puncak Perdana Library from customers' perspective and to determine most desired and critical dimension of quality services. Total number of 327 respondents participated, including a sample of 238 postgraduate and 89 undergraduate students of the Faculty of Information Management. The data revealed the different of minimum expectation, perception and expectation existed. The findings of this research was determined by the dimension that the "library as the place" as the most critical factor required for improvement across all the three dimensions of "LibQUAL" instrument, namely services affect, information control and library as place.